METODE KOMUNIKASI DAKWAH HABIB SYEKH BIN ABDUL QADIR ASSEGAF DALAM MENINGKATKAN BUDAYA SHALAWATAN DIKALANGAN JAMA’AH MAJLIS AHBAABUL MUSTHOFA SURAKARTA - Adi Rahma Saputra Maya Sekar Wangi, Buddy Riyanto (Solidaritas, 2018)
ABSTRACTThere is one of Ulama or Dai which spreading Islam by dakwah communication method as have done by Walisongo that is used art method long time ago. He is Habib Syekh bin Abdul Qadir Assegaf, who did not start his dakwah by using shalawatan art and he just get 200 jamaah/ congegation. But after he used shalawatan art, the congegations reached to fifteen thousands in his recitation of Islam.Metode Komunikasi Dakwah Habib Syekh Bin Abdul Qadir Assegaf dalam Meningkatkan Budaya Shalawatan Dikalangan Jama’ah Majlis Ahbaabul Musthofa Surakarta is a research which aimed to describe the method of dakwah communication by Habib Syekh bin Abdul Qadir Assegaf to increased shalawatan tradition in the congegation circle of jama’ah majlis Ahbaabul Musthofa Surakarta.This research using qualitative descriptive method with 8 informants, there are key informant by Habib Syekh himself, two delegation from Islam religion leader, two delegations of Ahbaabul Musthofa hadrah personel, and three delegations from Ahbaabul Musthofa congegation. This research did by interview, direct observation and documentation. Technique of data analysis used interactive data analysis technique there are data collection, data reduction, data presentation then conclusion. To measure the data validity, the researcher used triangulation sources technique, it is different informants but using the same technique.The result of this research showed that dakwah communication method which used by Habib Syekh bin Abdul Qadir Assegaf to increase shalawatan tradition in congegation circle of jamaah majlis Ahbaabul Musthofa Surakarta by speech method and art. Speech method include of Nasehat, Tabsyir ( good news for prophet Muhammad), Tandzir (warning), Wasiat and Kisah. Whereas art method of Habib Syekh in his dakwah activities with shalawatan art which is reflecting shalawat in qasidah style go along with hadrah or rebana music. Speech method and art is very effective to increase shalawatan tradition in the congengation circle of jamaah majlis Ahbaabul Musthofa, indicated by changing effect in the jamaah such as cognitive effect (knowledge) that happened in the jamaah whom can infiltrated the reading of shalawat which reflect. Affective effect (attitude) which indicated by emotional side of jamaah more be controled by theirselves, and behavioral effect (action) which indicated by the congegations that participated and competed to create hadrah group.keywords : communication, dakwah communication method, Shalawatan tradition